0250 Greater Slow Wave Activity in Pre-pubertal Children Is Associated With Less Negative Emotional Responses the Following Day. (25th May 2022) - Rech, Megan; Baran, Bengi; Myers, Annika; Palmer, Cara; Alfano, Candice
Abstract: Introduction: Inadequate sleep quantity and/or quality in children is known to forecast development of emotional problems, but how sleep microstructure relates to children's day-to-day emotional functioning remains unclear. Slow wave activity (SWA), or slow fluctuations of cortical activity during slow wave sleep (SWS) in the frequency range 0.75–4.5 Hz, is a marker of homeostatic sleep regulation and reflects synaptic reorganization of cortical areas early in life (Campbell & Feinberg, 2009). Findings regarding SWA among clinically depressed adolescents are mixed, with evidence of SWA reductions (Lopez et al., 2012) and increases (Tesler et al., 2016) compared to controls. Tesler et al. (2016) also showed SWA in frontal areas correlates positively with depressive thoughts. However, we are unaware of studies examining SWA in relation to depressive symptoms and next-day emotional responses among pre-pubertal children, before developmental declines in SWA (Jenni & Carskadon, 2004). Methods: We examined relationships between N3 SWA, depressive symptoms, and next-day emotional responses among N=17 un-medicated, healthy children ages 7-11 years (Tanner 1/2). Children completed a baseline assessment and one night of at-home PSG monitoring (10-hour sleep opportunity) then an in-lab emotional assessment the next day where they provided arousal and valence ratings for negative affective images from the International Affective Picture System. Analyses controlled for PSG night total sleep time, and SWA did not differ by gender. Results: Results indicated non-significant associations between SWA and child- and parent-reported depressive symptoms. Greater SWA density across frontal (r=-.66; p< .01), central (r=-.70; p< .001) and occipital regions (r=-.61; p< .01), along with frontal SWA amplitude (r=-.61; p< .01), significantly negatively related to valence ratings for negative images (images were rated as less negative). Conclusion: While preliminary, findings suggest potential relationships between SWA and emotional functioning in pre-pubertal children. We have previously shown greater SWS corresponds with less same-week negative affect among pre-pubertal anxious children (Palmer & Alfano, 2017); additionally, in a longitudinal study of pre-pubertal children at risk for depression, greater SWS in childhood protected against later development of depression (Silk et al., 2007). Collectively, findings suggest greater SWA prior to pubertal transition may buffer against negative daytime emotional experiences and later depression. Support (If Any):